If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -2(4 + -5) + -10 = 3(a + 7) + -18 Combine like terms: 4 + -5 = -1 32 + -2(-1) + -10 = 3(a + 7) + -18 Multiply -2 * -1 32 + 2 + -10 = 3(a + 7) + -18 Combine like terms: 32 + 2 = 34 34 + -10 = 3(a + 7) + -18 Combine like terms: 34 + -10 = 24 24 = 3(a + 7) + -18 Reorder the terms: 24 = 3(7 + a) + -18 24 = (7 * 3 + a * 3) + -18 24 = (21 + 3a) + -18 Reorder the terms: 24 = 21 + -18 + 3a Combine like terms: 21 + -18 = 3 24 = 3 + 3a Solving 24 = 3 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 24 + -3a = 3 + 3a + -3a Combine like terms: 3a + -3a = 0 24 + -3a = 3 + 0 24 + -3a = 3 Add '-24' to each side of the equation. 24 + -24 + -3a = 3 + -24 Combine like terms: 24 + -24 = 0 0 + -3a = 3 + -24 -3a = 3 + -24 Combine like terms: 3 + -24 = -21 -3a = -21 Divide each side by '-3'. a = 7 Simplifying a = 7
| -0.5d+4=10 | | 2x-2=-2 | | -4(x+2)+x=4 | | 9x+29=4x+1 | | -7=9-3n+5n | | 4x/3=18 | | (4x+7)(-7x+4)= | | -10x-4=11-7x | | -5x-4x+7=-5 | | 2x^4+18x^2+243=0 | | 5x+4x-8=1 | | 17+8-20=4(a-7)-3 | | 11-5= | | 4(2x-10)=-10(x-5) | | 3x+243=12x-9 | | 2x^4+18x^2-243=0 | | 218-2x=43x+23 | | Y=2x^2-16x+25 | | 17+2b-4c=4(a-7)-3 | | 192-6x=6x+12 | | y*12=-60 | | 7x+5-5x-2=11 | | 5a=0 | | 2x+2y+3z=3 | | 5y=13 | | -2x-5=x+7 | | -2w=-0,5 | | 4n^2-3n-13=0 | | 22(-c)=-66 | | 12-5x=2x^2 | | 33-16=8-16+5a+5 | | 12*5= |